The Online Harms White Paper: comparing the UK and German approaches to regulation. Issue 1 (2nd January 2019) - Theil, Stefan
ABSTRACT: The internet has revolutionised our ability to communicate and connect across historic social, political and geographic divides. Where previously gatekeepers mitigated and negotiated access to mass media platforms, today potentially anyone – and any content – can reach millions of users in an instant. This development bears great opportunities for the democratisation of expression and the diversification of public discourse but has likewise broadened the impact of harm caused online. This raises the question how platforms and services can be regulated effectively to combat online harms without jeopardising free and open discourse. The paper explores the Online Harms White Paper published by the UK Government earlier this year and compares its regulatory approach with the infamous German Network Enforcement Law.